Prevalence and determinants of diabetes retinopathy among non-insulin dependent diabetes mellitus patients seen at DOH's OPD-diabetes clinics in Metro Manila - Miguel-Baquilod, Marina
The development of visual loss in the form of retinopathy is a major concern in patients with diabetes, Insulin Dependent Diabetes Mellitus (IDDM) or Non-Insulin Dependent Diabetes Mellitus (NIDDM). It has become the number one cause of blindness among diabetics below the age of 60(9). The pathophysiologic mechanism of diabetes retinopathy is still unclear. The search for the true magnitude of the problem and its determinants are important in providing clues to the pathogenesis of retinopathy and the institution of appropriate preventive and management strategies. Several factors have been reported to be associated with the presence of diabetes retinopathy but findings in these studies are still inconclusive except for the duration of diabetes, which is the single, most consistently implied predictor of diabetes retinopathy. Other factors, have, up to now, no consistent data to support their role relative to diabetes retinopathy.This study was conducted in three selected Department of Health's Tertiary Hospitals Out-Patient Diabetes Clinics in Metro Manila with the following objectives: Firstly, estimation of the prevalence of diabetes retinopathy among adult NIDDM and; Secondly, identification of independent factors that are significantly associated with its presence. The first objective employed a cross-sectional study design which involved some 592 NIDDM patients (30 years and over). The prevalence of diabetes retinopathy was 41.9%. The second objective was investigated through a case-control study design which included all the prevalent cases determined in the cross-sectional ophthalmologic examination.The most significant independent factors identified through a univariate and multivariate analyses were duration of diabetes of 10 years or more and the use of insulin of over 6 months in the treatment of NIDDM. The association of the other factors with diabetes retinopathy can easily be explained by chance.The main outcome as shown by the logistic analysis is that the probability of having diabetes retinopathy of a middle aged NIDDM patient is 40% more than that of a young adult NIDDM. The probability of having diabetes retinopathy in elderly diabetic is 20% more than that of a young adult in an NIDDM whose disease duration is 10 years or more than in an NIDDM patient whose duration of diabetes is less than five years.The use of insulin in more than 6 months is associated with 2.5 times the risk of having diabetes retinopathy. However, the use of insulin among NIDDM is an index of the severity of the disease and its complications which may have necessitated its use; hence, the observed association does not necessarily reflect the effect of insulin per se on diabetes retinopathy.